외국인투자가 국내기업의 생산성에 미친 효과: 분위회귀 접근법 - 김재훈 (13565, 2014)
This study analyzes how heterogeneous across firms’ productivity level the effects of foreign direct investment (FDI) on the productivity of firms in a host country are. The study uses firm level data over 2000~2009 in South Korea and takes a quantile re